Recursive Subsystems in Aphasia and Alzheimer's Disease: Case Studies in Syntax and Theory of Mind - Bánréti, Zoltán; Hoffmann, Ildikó; Vincze, Veronika (Frontiers in Psychology, 2016)
The relationship between recursive sentence embedding and theory-of-mind (ToM) inference is investigated in 3 persons with Broca’s aphasia, 2 persons with Wernicke’s aphasia, and 6 persons with mild and moderate Alzheimer’s disease (AD). We asked questions of four types about photographs of various real-life situations. Type 4 questions asked participants about intentions, thoughts, or utterances of the characters in the pictures (“What may X be thinking / asking Y to do?”). The expected answers typically involved subordinate clauses introduced by conjunctions or direct quotations of the characters’ utterances. Broca’s aphasics did not produce answers with recursive sentence embedding. Rather, they projected themselves into the characters’ mental states and gave direct answers in the first person singular, with relevant ToM content. We call such replies ‘situative statements’. Where the question concerned the mental state of the character but did not require an answer with sentence embedding (“What does X hate?”), aphasics gave descriptive answers rather than situative statements. Most replies given by persons with AD to Type 4 questions were grammatical instances of recursive sentence embedding. They also gave a few situative statements but the ToM content of these was irrelevant. In more than one third of their well-formed sentence embeddings, too, they conveyed irrelevant ToM contents. Persons with moderate AD were unable to pass secondary false belief tests. The results reveal double dissociation: Broca’s aphasics are unable to access recursive sentence embedding but they can make appropriate ToM inferences; moderate AD persons make the wrong ToM inferences but they are able to access recursive sentence embedding. The double dissociation may be relevant for the nature of the relationship between the two recursive capacities. Broca’s aphasics compensated for the lack of recursive sentence embedding by recursive ToM reasoning represented in very simple syntactic forms: they used one recursive subsystem to stand in for another recursive subsystem.